The Psychometric Properties of the Norwegian version of Self-Perception Profile for Adolescents (SPPA) - Jozefiak, Thomas; Backer-Grøndahl, Agathe (PsykTestBarn, 2019)
Description: The «Self-Perception Profile for Adolescents» (SPPA), developed by Susan Harter at the University of Denver, USA, is a self-report instrument for measuring domain specific and global self-perception/self-esteem. In the early 1990’s, Lars Wichstrøm translated the SPPA into Norwegian, adapted it, and validated it in a large representative sample of Norwegian adolescents (13-20 years of age). SPPA is free of charge, with copy right by Wichstrøm. The target group includes both the general population and clinical samples. Adolescents evaluate their competence on six different domains of their self-perception (academic, social, athletic, physical, romantic, close friends), in addition to their global self-perception. It takes approximately ten minutes to complete the SPPA. There are no requirements in terms of competence for administrating and scoring the SPPA. Literature search: We included 33 Norwegian articles, of which 30 were based on studies with 100 participants or more. Most of these studies were conducted in the general population (representative school samples), and a few among youths in Residential Care institutions and clinical samples. There are cross –sectional and longitudinal studies available, and the age of the adolescents ranges from 12 to 31 years. Psychometrics: We found support for satisfying validity (construct-, convergent, discriminant, and predictive validity), as well as satisfying reliability as indicated by internal consistency. No studies reported on test-retest reliability, while a few studies documented sensitivity to change. Conclusion: We recommend the Norwegian version of the SPPA to be used in research. The instrument seems promising also for clinical purposes, but more studies on the SPPA in Norwegian clinical samples should be conducted for a clear conclusion